The impact of a silane pigment treatment on the properties of thickness-sensitive spectrally selective paints - Steinbücher, Miha (Acta chimica slovenica, 2017)
Thickness-sensitive, spectrally selective paints based on a silane treatment of pigments were prepared with different pigment- volume concentrations. The critical pigment-volume concentration was determined by means of electrochemical impedance spectroscopy, while the pigment particle size distribution was determined with ultrasound spectroscopy. The selectivity versus thickness relation of a paint with a near-critical pigment-volume concentration was studied spectroscopically through performance criteria. Its nonlinearity was shown to be related to the surface topography. This relation was further supported by hydrophobicity measurements. Heat-gathering tests in a simulated solar collector supported the spectroscopic determination of an optimal dry-film thickness.
Keywords: hidrofobnost; hydrophobicity; pigment treatment; pigmentno zdravljenje; spectral selectivity; spektralna selektivnost; topografija; topography; TSSS barve; TSSS paints